(untitled) (UNIZIK Journal of STM Education, 2019)
This study determined the effect of crossword puzzle game on secondary school students’ academic achievement in chemistry in Awka Education Zone of Anambra State, Nigeria. Three research questions and four null hypotheses guided the study. Quasi experimental research design was adopted for the study. Population of the study comprised all the 1,011 SSI students in the 15 government owned coeducational secondary schools in Awka Education Zone. A sample of 139 (53 males and 86 females) senior secondary one (SSI) chemistry students who were selected from two schools out of the 15 co-educational secondary schools in the zone using multistage sampling procedure were involved in the study. Chemistry Achievement Test (CAT) which was validated by experts in chemistry, measurement and evaluation was the instrument used for data collection. Kuder- Richardson Formula 20 (KR) reliability coefficient of 0.72 was established. Data were analysed using mean, standard deviation and Analysis of Covariance. The findings revealed that students who were exposed to use of crossword puzzle game achieved significantly higher than those taught using the conventional method. It was concluded therefore that the use of crossword puzzle game enhances students’ academic achievement in chemistry. Based on the findings, it was recommended among others that chemistry teachers should learn to incorporate crossword puzzle game in teaching because it will help to enhance students’ acquisition of problem solving abilities, and thus improve achievement.